ANALISIS PROFITABILITAS USAHA KERIPIK TAHU PADA INDUSTRI RUMAH TANGGA SOFIE DI KOTA PALU - Riandini Ika Pratiwi; Yulianti Kalaba (Agroland: Jurnal Ilmu-ilmu Pertanian, 2014)
Sofie home industry is the only tofu chips business in Palu City. The demand on chips production has been increasing but the home industry employer sometime sover look the expenditure for the costs incurred in the chips production. This study aimed to determine the profitability         of Sofie home industry in producing chips and to identify the capability of the home industry           to generate net income over equity. This research was conducted from May to July 2013 in which two respondents were determined purposively. Primary and secondary data collected were analyzed using a quantitative profitability analysis. The Gross Profit Margin GPM), the Net Profit Margin (NPM) and the ratio of Return on Invesment (RoI) found for the home industry were 62.37%, 53.61%, 16.82%, respectively, indicating that the profitability of the chips home industry is still low due to lack of attention to the costs incurred. The net income of the home industry was IDR 31,499,664 in 2012. The net income over equity capital produced by the industry was equal to 19.13% suggesting that the ability to generate a net profitusingits own capitalis very lowdue to high operating costs leading to profits achieved not comparable with the capital spent.